Analisis Perbaikan Tanah Lunak Pada Proyek Pembangunan Jalan Tol Probolinggo-Banyuwangi Paket 3 Dengan Berbagai Alternatif Metode Perbaikan Tanah - Muhammad Salman Mukhtar; Yerry Kahaditu Firmansyah; Bagas Aryaseta; Miguel Felix Wijaya (Universitas Muhammadiyah Surabaya, 2026)
The construction of Probolinggo–Banyuwangi Toll Road Package 3 faces geotechnical challenges due to variations in the thickness of compressible soft soil layers, which may cause excessive settlement and embankment instability. This study aims to analyze the influence of existing soil conditions on settlement and embankment stability and to determine the most appropriate ground improvement methods based on variations in compressible soil thickness. The research employed a quantitative method using secondary data, including Standard Penetration Test (SPT) data, embankment material parameters, ground improvement parameters, and seismic data for pseudostatic analysis. The N-SPT values were corrected and correlated into soil parameters, which were then modeled using PLAXIS 2D finite element software with the Hardening Soil model. The analysis results indicate that at STA 42+675, with a soft soil thickness of 5.5 m, the settlement difference under existing conditions was 16.22 cm and was successfully reduced to 7.9 cm after applying a combination of bamboo piles and bamboo mattress. At STA 45+700, with a soft soil thickness of 12 m, the existing condition experienced collapse during the embankment construction stage, whereas the combination of Prefabricated Vertical Drain (PVD) and preloading produced stable conditions with a settlement difference of 6.54 cm and a seismic safety factor of 1.375. This study concludes that selecting ground improvement methods based on the thickness of compressible soil layers can effectively improve embankment stability and control settlement.